Development of an international comorbidity education framework. (August 2017) - Lawson, C.; Pati, S.; Green, J.; Messina, G.; Strömberg, A.; Nante, N.; Golinelli, D.; Verzuri, A.; White, S.; Jaarsma, T.; Walsh, P.; Lonsdale, P.; et al.
Abstract: Context: The increasing number of people living with multiple chronic conditions in addition to an index condition has become an international healthcare priority. Health education curricula have been developed alongside single condition frameworks in health service policy and practice and need redesigning to incorporate optimal management of multiple conditions. Aim: Our aims were to evaluate current teaching and learning about comorbidity care amongst the global population of healthcare students from different disciplines and to develop an International Comorbidity Education Framework (ICEF) for incorporating comorbidity concepts into health education. Methods: We surveyed nursing, medical and pharmacy students from England, India, Italy and Sweden to evaluate their understanding of comorbidity care. A list of core comorbidity content was constructed by an international group of higher education academics and clinicians from the same disciplines, by searching current curricula and analysing clinical frameworks and the student survey data. This list was used to develop the International Comorbidity Education Framework. Results: The survey sample consisted of 917 students from England (42%), India (48%), Italy (8%) and Sweden (2%). The majority of students across all disciplines said that they lacked knowledge, training and confidence in comorbidity care and were unable to identify specific teaching on comorbidities. All student groups wanted further comorbidity training. The health education institution representatives found no specific references to comorbidity in current health education curricula. Current clinical frameworks were used to develop an agreed list of core comorbidity content and hence an International Comorbidity Education Framework. Conclusions: Based on consultation with academics and clinicians and on student feedback we developed an International Comorbidity Education Framework to promote the integration of comorbidity concepts into current healthcare curricula. Highlights: The number of people living with multiple conditions at the same time is rising. Health care and education systems usually focus on single diseases. Multidisciplinary students perceive that they lack understanding on comorbidity care. Comorbidity is not explicitly included within international health curricula. An international comorbidity education framework is proposed.